The collection of Allium L. at the South-Ural Botanical Garden–Institute - L. A. Tukhvatullina; L. M. Abramova (Труды по прикладной ботанике, генетике и селекции)
The article presents the results of introducing wild species. forms and varieties of Allium L. in the South-Ural Botanical Garden– Institute, Ufa. This genus is known for many useful plants – edible, medicinal and ornamental – and for its rare species requiring protection. The collection contains 111 taxa: 92 species, plus a number of onion cultivars and forms. It includes 7 species listed in the Red Book of Bashkortostan, 35 rare species from other regions of the ex-USSR, 2 rare species from the Red Book of the Russian Federation, and 19 endemic species.The collection serves as the basis for studying biological characteristics, agronomic and ornamental traits, reproduction and in vitro cultivation features, etc. Biochemical composition of introduced genotypes is also analyzed. Special attention is paid to the cultivation of rare onions as one of the methods of preserving their biodiversity – their reintroduction into natural habitats is possible on this basis. Most of onions introduced into the Bashkir Cis-Urals (65 species, 78 taxa in total) are stable in cultivation and possess valuable food and/or ornamental qualities, which makes it possible to recommend them for wider use in gardening and phytodesign.